Emission risks in processing and conversion of lignocellulose-based biocomposites - Nanci Ehman; Sandra Rodríguez Fabià; Julia Catalán; Gary Chinga-Carrasco (Composites Part C: Open Access)
Wood-derived components (e.g. fibers, lignin, nanofibers) are widely studied to develop thermoplastic biocomposites with, for example, improved mechanical properties and reduced global warming potential. Manufacturing of biocomposite products includes compounding and conversion processes (e.g., extrusion, injection molding, and 3D printing). These processes apply mechanical forces and heat to melt thermoplastic polymers and form a given product. However, in some cases, compounding and conversion stages may generate emissions of volatile organic compounds (VOC) and/or ultrafine particles (UFP) and we must consider their effects on human health. Additionally, due to the nano-dimensions cellulose nanofibers are considered UFP. Therefore, its impacts on human health should be evaluated, especially when dried for biocomposite production. This review provides an overview of emissions generated in the production line of lignocellulose-based biocomposites, considering: wood preprocessing, extrusion, 3D printing, and injection moulding. Emissions of VOCs and UFP were considered, including the occupational exposure limits according to the current regulations and the potential health effects associated with such emissions